2016
DOI: 10.5430/jnep.v7n2p84
|View full text |Cite
|
Sign up to set email alerts
|

Teaching nursing students to provide effective heart failure patient education using a peer teaching strategy

Abstract: Background/objective: Prelicensure nursing students possess minimal knowledge, skills, and confidence to provide effective, patient-centered transitional heart failure (HF) education to patients. This article evaluates a unique educational intervention designed to prepare nursing students to be more effective HF patient educators upon graduation. Methods: A pretest, posttest design and survey was used to evaluate a three-hour educational program. This program was offered to three different groups of students b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Avallone and Cantwell found that upper level nursing students were able to relate in a positive way to the lower level nursing students, resulting in decreased levels of anxiety and higher self-esteem and self-confidence for lower level students. [17] 2. DESCRIPTION OF PROJECT…”
Section: Peer Mentoringmentioning
confidence: 99%
“…Avallone and Cantwell found that upper level nursing students were able to relate in a positive way to the lower level nursing students, resulting in decreased levels of anxiety and higher self-esteem and self-confidence for lower level students. [17] 2. DESCRIPTION OF PROJECT…”
Section: Peer Mentoringmentioning
confidence: 99%